2019
DOI: 10.26480/gwk.01.2019.01.04
|View full text |Cite
|
Sign up to set email alerts
|

A Study on Use of Rice Husk Ash in Concrete

Abstract: The rice husk is an agricultural waste which is obtained from milling process of paddy and approximately 22% of the weight of paddy is rice husk. The waste is used as fuel in producing stream in parboiling process. The 25 % the weight of husk is converted into ash which is known as rice husk ash (RHA) and is again a waste which is disposed. This ash consists of amorphous silica which can be used as pozzolana in making concrete and cement instead of disposing it without compromising on the properties of cement … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
19
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 30 publications
(19 citation statements)
references
References 4 publications
(4 reference statements)
0
19
0
Order By: Relevance
“…The results of this study showed that consistent with the soil with adding phenanthrene. The direct effects of CO2 and O3 on the leaf tissue of vegetables might promote or interfere with the secretion of root substances through affecting the photosynthesis of leaves, thus causing the change of coil microecological environment (Wang et al, 2014;Cheng et al, 2011;Gautam et al, 2019). Soil phenanthrene affect directly on the root system of vegetables, and its target organs are different from CO2 and O3.…”
Section: Elevated Atmospheric Co2 Or/and O3 Induce Changes In the Physical And Chemical Properties And Enzyme Activities Of The Soil Withmentioning
confidence: 99%
“…The results of this study showed that consistent with the soil with adding phenanthrene. The direct effects of CO2 and O3 on the leaf tissue of vegetables might promote or interfere with the secretion of root substances through affecting the photosynthesis of leaves, thus causing the change of coil microecological environment (Wang et al, 2014;Cheng et al, 2011;Gautam et al, 2019). Soil phenanthrene affect directly on the root system of vegetables, and its target organs are different from CO2 and O3.…”
Section: Elevated Atmospheric Co2 Or/and O3 Induce Changes In the Physical And Chemical Properties And Enzyme Activities Of The Soil Withmentioning
confidence: 99%
“…In another work, Franceschini et al prepared covalently bonded polymer C–S–H composite with the formation of covalent linkages between polymer and C–S–H phases by grafting trialkoxysilane (T-silane) and methyldialkoxysilane (D-silane) to the polymer chains [ 19 ]. To sum up, there are some attempts for the development of cement mixes by using rice husk ash as an alternative additive and direct or partial replacing with silica [ 20 , 21 , 22 , 23 ] and also most of the published works are mostly focused on the enhancement of strength properties of cementitious composites [ 24 , 25 ]. Besides, the effect of functionalized RHA by silane coupling agents on thermal and mechanical properties of thermoplastic composites was investigated to improve interfacial interactions in the composite structure [ 26 ].…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, collaboration in the field of civil engineering with the field of social science, such as human geography, is one of the alternatives to face challenges in the future. The type of building material has accommodated the importance of environmental sustainability; for example, many types of research have begun to consider renewable raw materials such as bamboo and husk ash as a mixture of concrete [1][2][3][4][5]. How about human society changes and culture?…”
Section: Introductionmentioning
confidence: 99%